The effect of eight weeks of sling-based training with rotational core exercises on ball velocity in female team handball players - Dahl, K. S.; van den Tillaar, R. (Journal of Human Kinetics, 2021)
The purpose of this study was to investigate whether sling-based training focused on rotational exercises would improve shooting performance in outfield handball players during the competitive season, and whether changes in performance were related to altered levels of core strength and rotational velocity. Twenty-five female outfield handball players (mean age 19.5 ± 2.0 years, height 1.72 ± 0.06 m, body mass 71.5 ± 8.6 kg, training experience 10.3 ± 2.4 years), performed 7 m shots, with and without a run-up, and jump shots. Maximal ball velocity, peak rotational velocity of the trunk with different loads and 1RM in a core strength test were measured before and after an 8-week training intervention. Players were divided into a sling-based and a plyometric/sprint training (control) group that trained three times per week for 8 weeks. The main findings were that sling-based training increased ball velocity by on average 3.2% across three techniques tested, while shooting performance decreased by 3% in the control group. However, both training groups demonstrated increased peak rotational velocity with different loads, but not the calculated 1RM core strength after the training period. It was concluded that sling-based training with rotational core exercises could improve maximal ball velocity in female handball players during a competitive season by around 3%. However, this increased ball velocity may have been caused by increased angular velocity in the core, rather than absolute maximal core strength. It is suggested that sling-based training has impacted timing variables of the different involved segments, or possibly power transfer between segments, which may explain the enhancement in ball velocity.